Identity mapping strategies-cum-ideologies in selected Yoruba Christian songs among Yoruba Christians in Nigeria - Michael, Ajayi Temitope (Journal of Modern Languages, 2017)
Ideology and identity are two inseparable phenomena that characterise the existence of mankind. As human beings, even when we share a common identity as a people of the same faith, members of the same family, and members of the same society, there are certain ways through which we either consciously or unconsciously create different identities for ourselves; a reflection of our cultural ideologies. This paper examines how Yoruba Christian songs are employed by Yoruba Christian faithful in Nigeria to identify with Yoruba belief system while mapping different individualistic identities among themselves. Employing Staszak’s concept of Otherness, which is an ideological phenomenon inherent in the Yoruba cultural system, for data analysis, we discovered that although Yoruba Christiansin Nigeria identify with the generic reference term of ‘brethren’ in their gatherings, they still create different individualistic identities, Self and Other, for themselves through their songs. Similarly, they identify with some aspects of the Yoruba ideological belief system, as evidenced by the selected songs.